A multicentre, international, observational study on transarterial chemoembolisation in colorectal cancer liver metastases: Design and rationale of CIREL. Issue 8 (August 2020) - Pereira, Philippe L.; Arnold, Dirk; de Baère, Thierry; Gomez, Fernando; Helmberger, Thomas; Iezzi, Roberto; Maleux, Geert; Prenen, Hans; Sangro, Bruno; Nordlund, Anders; Zeka, Bleranda; Bauer, Robert; et al.
Abstract: Background: About 70–80% of patients with colorectal liver metastases appear as ineligible for a curative treatment approach. Transarterial chemoembolisation (TACE) using irinotecan-eluting beads has emerged as a promising treatment option in cases with irresectable liver metastases. Despite being in clinical practice for years, little is known about the treatment characteristics and outcomes when used as per routine hospital practice. Methods: Patients with hepatic metastases from colorectal cancer origin, admitted to contributing centres to receive TACE with drug-eluting LifePearl® Microspheres loaded with irinotecan, as part of their standard care, will be consecutively added to the registry. Data will be collected until the end of study, loss to follow-up or death. Primary endpoint is the characterisation of the treatment usage at the selected sites in Europe. Secondary endpoints include outcome parameters, safety and toxicity, as well as quality of life. Conclusion and AIMS: This multicentre, international, prospective observational study conducted in European centres plans to collect real-life data. This data will form an evidence-base from which conclusions can be drawn on how to improve patient selection and optimise treatment protocols when treating with TACE using irinotecan-eluting microspheres. Trial registration NCT03086096